Valutare le strategie di apprendimento negli studenti universitari: primi risultati di una ricerca valutativa condotta all'Università di Bologna - Elena Luppi; Stefano Benini (LED Edizioni Universitarie, 2017)
This paper moves from an educational evaluation research conducted in the on the Nursery Degree Programme of Bologna University. Starting from the analysis of transversal competences that are crucial for nurses and from the outcomes of a qualitative exploratory phase of the research, this contribution is focused on the assessment of students' learning strategies, at the beginning and at the end of the degree programme. Such assessment has been conducted through the application of «Learning Strategies Questionnaire QSA», validated from Pellerey in 1996 to 168 students at the first and last year (160 students) of the Nursery Degree Programme. In the meanwhile the questionnaire has been proposed to almost 100 first year University students from other degree programmes and 390 Secondary School's students. Thanks to this second and third sample, results could be compared with the standard group through which the questionnaire was validated in 1996 and with other students attending University and Secondary School nowadays. The results put into evidence a certain urgency in reflecting on learning strategies proficiency for students in the last 20 years: in fact the scores of University students now do not appear so far from the results of the students aged 15 in 1996.